2021
DOI: 10.1136/bmjopen-2020-047715
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a systematic review assessing ambulatory vital sign monitoring impact on deterioration detection and related clinical outcomes in hospitalised patients

Abstract: IntroductionAmbulatory monitoring systems (AMS) can facilitate early detection of clinical deterioration, and have the potential to improve hospitalised patient outcomes. The objective of this systematic review is to assess the impact of vital signs monitoring on detection of deterioration and related outcomes in hospitalised patients using AMS, in comparison with standard care.Methods and analysisA systematic search was conducted on 27 August 2020 in MEDLINE, Embase, CINAHL, Cochrane Database of Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For randomised controlled trials the Cochrane risk of bias tool (RoB2) was used [ 23 ]; for non-randomised studies, the Newcastle Ottawa Scale (NOS) [ 24 ] and the “Risk Of Bias In Non-randomised Studies—of Interventions” (ROBINS-I) were applied [ 25 ]; and, in addition, the Mixed Methods Appraisal tool (MMAT) [ 26 ] was used for all studies. This was a change from the original protocol [ 19 ] as the Jadad scale was replaced by the ROBINS-I for assessment of non-randomised studies, as we found it more comparable with the ROB2 tool used for included RCTs. Two reviewers (CA and CB) independently appraised each study and disagreements were solved by discussion until consensus was reached with a third reviewer (SV).…”
Section: Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…For randomised controlled trials the Cochrane risk of bias tool (RoB2) was used [ 23 ]; for non-randomised studies, the Newcastle Ottawa Scale (NOS) [ 24 ] and the “Risk Of Bias In Non-randomised Studies—of Interventions” (ROBINS-I) were applied [ 25 ]; and, in addition, the Mixed Methods Appraisal tool (MMAT) [ 26 ] was used for all studies. This was a change from the original protocol [ 19 ] as the Jadad scale was replaced by the ROBINS-I for assessment of non-randomised studies, as we found it more comparable with the ROB2 tool used for included RCTs. Two reviewers (CA and CB) independently appraised each study and disagreements were solved by discussion until consensus was reached with a third reviewer (SV).…”
Section: Methodsmentioning
confidence: 95%
“…This review was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist (Additional file 1 : Appendix 1) [ 18 ]. The full systematic review protocol was published prospectively [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations